Dye sensitized solar cell (DSSC) by a novel fully room temperature process: a solar paint for smart windows and flexible substrates - Agarkar, Shruti A.; Dhas, Vivek V.; Muduli, Subas; Ogale, Satishchandra B. (RSC Advances, 2012)
We report the development of a titania-nanoparticle-based solar paint which gives a conversion efficiency of 3.6% on FTO/glass substrates under fully room temperature processing. The paint cures quickly saving time in the cell fabrication process. Even on a flexible ITO/PET substrate efficiency of 2.4% was achieved. We present and analyze the results of described materials and device property characterizations.